Digital transformation of the Certis group: Delivering beyond security services - Miller, Steven M. (Institutional Knowledge at Singapore Management University, 2021)
Set in 2021, this case describes the Certis Group’s transformation journey from a traditional physical guarding service provider to an advanced provider of integrated operations technology services for security, facilities, visitor management, and other types of monitoring related businesses. Certis started in 1958 as a Singapore government unit for auxiliary police, and restructured into a private commercial entity in 2005. They grew to a US$1.1 billion multinational with an overseas presence in six countries and territories, while leading their home market. Their digital transformation was enabled by a platform created for orchestrating Internet-of-Things sensor streams with Artificial Intelligence-enabled analytics, centralized command and control, and workforce coordination and communication. This new “Security+” approach to delivery made it possible for Certis to scale beyond prior limits, integrate across multiple service lines, and offer new types of services. They began rolling out Security+ solutions in 2018 starting with Singapore’s iconic Jewel Changi Airport, a 10-storey megamall, and expanded to other large multi-use facilities and industrial zones. Paul Chong, President and Group CEO since 2004 was keenly aware that competitors saw the success Certis was having with its digital transformation and platform-based approach. What could be their path forward for developing their next generation of delivery capabilities to drive further growth locally and overseas? This case illustrates how a formerly traditional and inherently physical service provider can harness technology and digital transformation to drive growth through innovation. Students will develop an understanding of how leaders can drive organizational transformation and capability development. They can discuss how to identify the talent acquisition, training and execution strategies needed to make these changes, and how to sustain ongoing competitive advantage.